The Relationship between Learning Styles and ProblemSolving Strategies in Undergraduate Nursing Students of Isfahan University of Medical Sciences Iran - Reyhaneh Taheri; Fariba Karimi (Kerman University of Medical Sciences, 2017)
Background & Objective: Individuals based on their learning styles have different interpretation of the environment and issues and choose different problemsolving strategies The objective of the present research was identifying the relationship between learning methods and problemsolving strategies among students of the bachelor of nursing in Isfahan University of Medical Sciences Iran Methods: The present study was a correlational research The statistical population included students of the bachelor of nursing in Isfahan University of Medical Sciences in 20132014 (n = 380) From among them 191 individuals were selected through cluster random sampling and based on sample size determined using Cochran`s sample size formula The data collection tools included Kolbs Learning Styles Inventory (LSI) and the ProblemSolving Approaches Questionnaire (Cassidy & Long) The face validity of the questionnaires was accepted due to their high application rate The reliability of the questionnaires was estimated as more than 070 Data were analyzed using stepwise regression and the Pearson correlation coefficient Results: The results showed an inverse relationship between experiential learning style and constructive problemsolving style In addition there was a direct relationship between experiential learning style and nonconstructive problemsolving style There was a reverse relationship between abstract conceptualization and nonconstructive problemsolving style The best predictor of constructive and nonconstructive problemsolving styles was experiential learning style Conclusion: Based on the relationship observed between learning styles and problemsolving styles it is suggested that learning styles and practices be introduced to students and teachers in training courses so that they use suitable problemsolving styles based on the identified learning styles Moreover the provision of nursing courses that provide the possibility of experiential learning for students is highly recommended